Peningkatan Kompetensi Guru Bahasa Inggris SD dalam Penerapan P5 Kurikulum Merdeka - Kurniawan Yudhi Nugroho; Muh Syafei; Mega Mulianing Maharani; Hartono Hartono; Choiril ANwar (Universitas Muria Kudus, 2025)
This Community Service Program (PkM), designed to span one year, aims to enhance the competencies of elementary school English teachers in implementing the Pancasila Student Profile Strengthening Project (P5) within the framework of the Merdeka Curriculum. The program addresses various challenges teachers face in understanding and effectively applying the P5 concept in learning activities. A qualitative method with a case study approach was employed to assess the program's impact, utilizing data collected through interviews, observations, and analysis of teacher lesson plan documents. The findings indicate that participants demonstrated significant improvement in their understanding and application of the P5 concept in classroom settings during the implementation of PkM activities. Teachers were able to design and execute project-based learning aligned with the values of Pancasila and the Merdeka Curriculum. Classroom observations revealed increased student engagement in the learning process. Moreover, teachers showed greater confidence in integrating character education into their teaching. In conclusion, intensive training and mentoring effectively improved teachers’ competencies in implementing the Pancasila Student Profile Strengthening Project. This progress significantly supports the successful implementation of the Merdeka Curriculum in the participating elementary schools. The outcomes of this program are expected to contribute to the development of teacher training models that can support broader educational programs.